Site tenacity and turnover rate of staging and wintering Bean Geese Anser fabalis in southern Sweden - Nilsson, Leif; Persson, Hakon (Wildfowl, 1991)
Site tenacity and turnover rate among staging and wintering Bean Geese were studied by observing neck-banded individuals in southern most Sweden. Bean Geese from different breeding areas in northern Finland and in southern Sweden were found on all sites, but in significantly different proportions. Most individuals showed a marked site tenacity, 69% being seen at only one site in the same season. Bean Geese recorded during two consecutive seasons were generally seen in the same area. About 50% of Finnish-marked Bean Geese stayed for less than ten days, the longest period being 120 days. Southwest Skane functioned as a major staging and wintering area for an appreciable Bean Goose population while simultaneously serving as a more short-term stopover area for Bean Geese on passage.